Combination of GD2-directed bispecific trifunctional antibody therapy with Pd-1 immune checkpoint blockade induces anti-neuroblastoma immunity in a syngeneic mouse model - Ivasko, Sara Marie; Anders, Kathleen; Grunewald, Laura; Launspach, Michael; Klaus, Anika; Schwiebert, Silke; Ruf, Peter; Lindhofer, Horst; Lode, Holger N.; Andersch, Lena; Schulte, Johannes H.; Eggert, Angelika; et al. (Frontiers in Immunology, 2023)
Despite advances in treating high-risk neuroblastoma, 50-60% of patients still suffer relapse, necessitating new treatment options. Bispecific trifunctional antibodies (trAbs) are a promising new class of immunotherapy. TrAbs are heterodimeric IgG-like molecules that bind CD3 and a tumor-associated antigen simultaneously, whereby inducing a TCR-independent anti-cancer T cell response. Moreover, via their functional Fc region they recruit and activate cells of the innate immune system like antigen-presenting cells potentially enhancing induction of adaptive tumor-specific immune responses. We used the SUREK trAb, which is bispecific for GD2 and murine Cd3. Tumor-blind trAb and the monoclonal ch14.18 antibody were used as controls. A co-culture model of murine dendritic cells (DCs), T cells and a neuroblastoma cell line was established to evaluate the cytotoxic effect and the T cell effector function in vitro. Expression of immune checkpoint molecules on tumor-infiltrating T cells and the induction of an anti-neuroblastoma immune response using a combination of whole cell vaccination and trAb therapy was investigated in a syngeneic immunocompetent neuroblastoma mouse model (NXS2 in A/J background). Finally, vaccinated mice were assessed for the presence of neuroblastoma-directed antibodies. We show that SUREK trAb-mediated effective killing of NXS2 cells in vitro was strictly dependent on the combined presence of DCs and T cells. Using a syngeneic neuroblastoma mouse model, we showed that vaccination with irradiated tumor cells combined with SUREK trAb treatment significantly prolonged survival of tumor challenged mice and partially prevent tumor outgrowth compared to tumor vaccination alone. Treatment led to upregulation of programmed cell death protein 1 (Pd-1) on tumor infiltrating T cells and combination with anti-Pd-1 checkpoint inhibition enhanced the NXS2-directed humoral immune response. Here, we provide first preclinical evidence that a tumor vaccination combined with SUREK trAb therapy induces an endogenous anti-neuroblastoma immune response reducing tumor recurrence. Furthermore, a combination with anti-Pd-1 immune checkpoint blockade might even further improve this promising immunotherapeutic concept in order to prevent relapse in high-risk neuroblastoma patients.